2022
DOI: 10.5539/jel.v11n4p84
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Teaching Anxiety, Teaching Self-Efficacy, and Problems Encountered During the Practice Teaching Course

Abstract: Practice teaching represents authentic experiential learning and culminating experience to better prepare the prospective teachers for actual teaching experience. However, pre-service teachers who go through the practicum have a number of worries and anxieties which could lower their teaching self-efficacy and consequently their performance. This study aimed to determine the relationship between the pre-service teachers’ teaching anxiety and teaching self-efficacy, the possible reasons for such teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
2
6
1
Order By: Relevance
“…In a study of Ngidi & Sibaya (2003), they emphasized that gender, age and grade placement causes anxiety among practice teachers. While other works suggest that practice teachers in higher grade levels experience lesser anxiety (Gorospe, 2022), but the findings of this paper suggest otherwise. Likewise, in dealing with cooperating teachers, the female practice teachers experience higher www.rsisinternational.org levels of anxiety compared with their male counterparts.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In a study of Ngidi & Sibaya (2003), they emphasized that gender, age and grade placement causes anxiety among practice teachers. While other works suggest that practice teachers in higher grade levels experience lesser anxiety (Gorospe, 2022), but the findings of this paper suggest otherwise. Likewise, in dealing with cooperating teachers, the female practice teachers experience higher www.rsisinternational.org levels of anxiety compared with their male counterparts.…”
Section: Discussioncontrasting
confidence: 82%
“…This is also true with the claim of Ngidi & Sibaya (2003), that gender causes anxiety among practice teachers. While some papers suggest that gender does not have any correlate with practice teaching anxiety (Albasin-Lacaba, et.al, 2022), but the cooperating teacher's expectations from the practice teachers causes their anxiety (Gorospe, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety in this study is viewed from the dimensions of physical, behavioral, and cognitive. Many previous studies reported that students experienced anxiety during their college years [11,12,14,22,23]. Our data suggested that most students experienced very severe anxiety (panic) during the webinar tutorial.…”
Section: Learning Difficulties and Anxiety Levels During The Webinar ...supporting
confidence: 50%
“…A study related to student anxiety is mostly carried out in study programs or courses that contain practicum, practice, presentation, and or complex calculations, such as in the field of medicine, nursing, language, statistics, mathematics, microteaching, and pre-service teachers [6][7][8][9][10][11][12][13][14][15][16][17][18]. However, there is a limited study examining the anxiety of students attending distance learning who also have a job.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher self-efficacy is an important factor in future teaching practices and is related to teacher effectiveness and student learning (Naidoo (Naidoo & Naidoo, 2023). In teacher education programs, most prospective teachers in practicum have a number of concerns and anxieties that can reduce self-efficacy and have an impact on their performance (Gorospe, 2022). The loading factor in creating a learning environment is 0.767 ; this states that through knowledge from research results, teachers can create a learning environment that improves students' thinking skills.…”
Section: Discussionmentioning
confidence: 99%